2004
DOI: 10.1105/tpc.104.024968
|View full text |Cite
|
Sign up to set email alerts
|

β-1,3 Glucan Sulfate, but Not β-1,3 Glucan, Induces the Salicylic Acid Signaling Pathway in Tobacco and Arabidopsis

Abstract: Sulfate substituents naturally occurring in biomolecules, such as oligosaccharides and polysaccharides, can play a critical role in major physiological functions in plants and animals. We show that laminarin, a b-1,3 glucan with elicitor activity in tobacco (Nicotiana tabacum), becomes, after chemical sulfation, an inducer of the salicylic acid (SA) signaling pathway in tobacco and Arabidopsis thaliana. In tobacco cell suspensions, the oxidative burst induced by the laminarin sulfate PS3 was Ca 2þ dependent bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
146
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(157 citation statements)
references
References 63 publications
6
146
2
3
Order By: Relevance
“…Other studies have reported that basic defenses of A. thaliana to B. cinerea depend mostly on JA and ET [16,17,39]. Nevertheless, SA-induced plant defenses were also reported to be involved against necrotrophs in A. thaliana [39][40][41] and tobacco [42]. Perhaps a difference with the studies cited above and our results is that we have tested the hormone dependence of elicitor-triggered defenses in contrast to hormone-dependence of basal resistance without elicitor pretreatment.…”
Section: Ases Induces Plant Defenses Against B Cinerea Via Sa- Jaancontrasting
confidence: 59%
“…Other studies have reported that basic defenses of A. thaliana to B. cinerea depend mostly on JA and ET [16,17,39]. Nevertheless, SA-induced plant defenses were also reported to be involved against necrotrophs in A. thaliana [39][40][41] and tobacco [42]. Perhaps a difference with the studies cited above and our results is that we have tested the hormone dependence of elicitor-triggered defenses in contrast to hormone-dependence of basal resistance without elicitor pretreatment.…”
Section: Ases Induces Plant Defenses Against B Cinerea Via Sa- Jaancontrasting
confidence: 59%
“…For example, Ménard et al (2004) demonstrated that laminaran, with eliciting activity in tobacco and A. thaliana, after its sulfation, becomes an inducer of the salicylic acid (SA) pathway.…”
Section: Laminaransmentioning
confidence: 99%
“…This water-soluble molecule is composed by glucose units with linkages β(1→3) and β(1→6) in a ratio of 11:1. Laminaran has an average polymerization degree of 25 glucose units and three simple ramifications of β-glucose at the C-6 position (Read et al, 1996;Ménard et al, 2004).…”
Section: Laminaransmentioning
confidence: 99%
“…Arabidopsis plants expressing the nahG gene and infected with B. cinerea show larger lesions compared with wild-type plants (Govrin and Levine, 2002). In tobacco (Nicotiana tabacum), acidic isoforms of PR3 and PR5 gene that are specifically induced by SA (Ménard et al, 2004) are up-regulated after challenge by B. cinerea (El Oirdi et al, 2010). Resistance to some necrotrophs like Fusarium graminearum involves both SA and JA signaling pathways (Makandar et al, 2010).…”
mentioning
confidence: 99%
“…In these experiments, we chose NahG plants that totally degrade SA to be sure that no remaining traces of SA would be detected after RLs treatment and before protection assays (Heck et al, 2003;Ménard et al, 2004;Ferrari et al, 2007). We also used sid2 plants that are impaired in SA synthesis (Nawrath and Métraux, 1999;Wildermuth et al, 2001), npr1 that is insensitive to SA (Cao et al, 1994), and ein2 mutants that are insensitive to ET (Guzmán and Ecker, 1990).…”
mentioning
confidence: 99%